Desenvolvimento de métodos ópticos analíticos baseado na fluorescência multidimensional para quantificar biodiesel em blendas de diesel-biodiesel’ - Fernando Rodrigues da Conceição (2024)
In this work, the unpolarized (MEENP) and polarized (MEEP) excitation-emission matrices of undiluted (BDBND) and diluted (BDBD) diesel-biodiesel blends were analyzed using the parallel factor analysis method (PARAFAC). Through this analysis, analytical models to predict the biodiesel content in BDBND and BDBD were constructed. Regarding the PARAFAC analysis of the MEENP of the BDBND (MEENP-BDBND), the loadings values related to the concentration were used to construct the pseudo-univariate model. This model presented limits of detection (LOD) and limit of quantification (LOQ) of 2.5% and 11% w/w, respectively. According to the values of the root mean square error of predictions (RMSEP) and relative standard deviation of prediction (RSDP), the pseudo-univariate model showed robustness in predicting biodiesel in the samples from the external validation set, with values between 0.53-0.70% w/w and 3.65-5.10%, respectively. For the analysis of the MEEP of BDBND (MEEP(ND)) and BDBD (MEEP(D)), PARAFAC was applied to evaluate the best excitation-emission variables for the construction of polarized analytical models. Additionally, polarized 2D fluorescence measurements of external validation samples were used to validate the polarized models. For MEEP(ND), the best analytical curves were obtained in HV and HH polarizations, with LOD values equal to 1.05% w/w and 0.12% w/w while the LOQ values were 3.31% w/w and 0.38% w/w, respectively. In relation to the predicted biodiesel content, the model obtained in HV polarization presented the best RMSEP and RSDP values, which were 0.32% w/w and 2.14%, respectively. Regarding MEEP(D), all analytical curves showed low LOD and LOQ values. However, only the model obtained in VV polarization presented the best RMSEP and RSDP values, which were 0.49% w/w and 3.24%, respectively. Therefore, according to the RMSEP and RSDP values, the best analytical optical model was obtained through the analysis of MEEP(ND) with PARAFAC, in HV and HH polarizations. In addition to analytical optical models, the molecular properties of BDBD were evaluated using anisotropy resolved multidimensional emission spectroscopy (ARMES). As a result, anisotropy maps were constructed and showed low fluorescence anisotropy values of the fluorophores that belong to BDBD. These low fluorescence anisotropy values were attributed to rotational depolarization of the fluorophores. Keywords: Biodiesel; Diesel; Quantification; EEM; EEMp; PARAFAC; ARMES